Symptom presentation, perceived causes, and help-seeking practices among adults receiving depression or anxiety care in Nepal: A qualitative study - Nagendra P. Luitel; Kriti Pudasaini; Bishnu Lamichhane; Kamal Gautam; Mark J.D. Jordans (PLoS ONE, 2026)
Depression and anxiety are prevalent worldwide, yet fewer than 20% of individuals in low- and middle-income countries receive appropriate care. Cultural norms play a significant role in how symptoms are expressed and how individuals seek help. In Nepal, traditional healers are often preferred over mental health specialists. This qualitative study explored how symptom presentation and perceived causes impact treatment-seeking behaviour among adults receiving care for depression or anxiety. Twenty-four participants (13 with depression, 9 with anxiety, and 2 with both conditions) were recruited from Jhapa, Chitwan, and Kailali districts through primary healthcare providers, psychosocial counselors, and mental health specialists. Individual interviews were conducted using the adapted McGill Illness Narrative Interview (MINI) to explore symptom experiences, illness narratives, perceived causes, and help-seeking patterns. Thematic analysis of the data was done using NVIVO software. Participants reported a range of emotional, cognitive, and physical symptoms including fear, anxiety, restlessness, irritability, sadness, and hopelessness. Somatic complaints like headaches, fatigue, and gastrointestinal issues were often interpreted as consequences of psychological stress. Some participants described dissociative experiences, such as detachment, amnesia, or perceptual distortions, leading to panic or self-harm. Stressors mentioned included financial hardships, bereavement, family conflicts, trauma, and culturally ingrained fears. Most participants initially sought help from biomedical providers like private clinics, hospitals, health centers, or health camps with some also consulting traditional healers. Education and caste played a significant role in treatment choices, with individuals with higher education and from higher castes more likely to seek biomedical care first. Gender and age had minimal impact. The study underscores the importance of culturally sensitive, community-based mental health programs to reduce stigma and ensure equitable access to care for depression and anxiety in Nepal.